Louiz Zamperini's American Dreams as Reflected in the Film Unbroken - Khairiah, Masruriati (COMMICAST, 2020)
In this undergraduate thesis describes about American dream and motivation theory. This is aiming at analyzing motivation’s role in human life to fulfill their needs by focusing to the main character. The concept of American dream can be seen in Louis Zamperini as the main character of this film in principle of life. Hence, this undergraduate thesis has two main objectives to describe the Louis Zamperini’s dreams and to analyze Louis Zamperini’s motivation in his survival as the prisoner of Japan as reflected in the film Unbroken.This research is under a descriptive qualitative method. Therefore, library research is used for compiling both primary data and secondary data. The primary data is adopted from the film, meanwhile the secondary data refer to some sources, such as books, journals, articles, and on-line data from internet. Method of American studies as an interdisciplinary approach is also applied along with theories to analyze the problem formulation in this research. After the data are collected, they are analyzed by using the psychological study approach, and focuses on theory Hierarchy Needs of Abraham Maslow. Maslow’s theory explained the description of motivation based on needs. The hierarchy dividing to physiological needs, safety needs, love needs, esteem needs, and needs for self-actualization. Then, the writer uses American dream concept such as the dream of good life, liberty, and pursuit of happiness.The results of this research, the researcher found that Louis Zamperini as the main character what he did in life, there is a motivation that supports him to reach his dream like other immigrants who came to America using this concept in general. The American dream and motivation are still adopted in some American films as popular culture. Hence, it proves that American dream still exists with different style like media of film.